Features of the novel coronavirus infection in cancer patients - A. D. Makatsariya; I. Elalamy; B. Brenner; A. V. Vorobev; L. A. Ashrafyan; E. V. Maslenkova; V. O. Bitsadze; J. Kh. Khizroeva; A. S. Shkoda; A. G. Solopova; V. N. Galkin; J.-C. Gris (Акушерство, гинекология и репродукция, 2022)
A novel coronavirus (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) is largely associated with various coagulopathies, which can lead to either bleeding and thrombocytopenia or hypercoagulation and thrombosis. Thrombohemorrhagic complications also could accompany the development of cancer process. In addition, circulating inflammatory biomarkers such as fibrin, D-dimer, P-selectin and von Willebrand factor (vWF) typical to both coronavirus infection and malignancy process are of special interest. In this review, we discuss potential interplay between COVID-19 and cancer related to endothelial dysfunction, platelets, and systemic inflammatory response syndrome. Most importantly, patients should be treated in early stage of the disease process when elevated levels of fibrinogen, D-dimer, vWF, and P-selectin are observed. The level of these markers will rise rapidly upon disease progression, followed by a cytokine storm, would evidence about a poor prognosis.